New Target for Minoxidil in the Treatment of Androgenetic Alopecia - Shen Y; Zhu Y; Zhang L; Sun J; Xie B; Zhang H; Song X (Dove Medical Press, 2023)
Yuqing Shen,1 Yuqi Zhu,1 Li Zhang,1 Jiayi Sun,1 Bo Xie,2 Hongyan Zhang,2 Xiuzu Song2 1Department of Dermatology, Hangzhou Third People's Hospital, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 2Department of Dermatology, Hangzhou Third People's Hospital, Affiliated Hangzhou Dermatology Hospital of Zhejiang University School of Medicine, Hangzhou, People's Republic of ChinaCorrespondence: Xiuzu Song, Hangzhou Third People's Hospital, Hangzhou, People's Republic of China, Email songxiuzu@sina.comObjective: To investigate the mechanism of minoxidil in treating androgenetic alopecia (AGA).Methods: The mechanism of action of minoxidil on AGA was first systematically investigated from the viewpoint of network pharmacology, including minoxidil-AGA target prediction, protein-protein interaction (PPI) network analysis, molecular docking and enrichment analysis of targets related to minoxidil and AGA, and dermal papilla cell assays to confirm the viability of prediction.Results: The combined analysis revealed that minoxidil treatment of AGA not only acts on androgenic receptors (AR) but also on 2 new targets, steroid 17-alpha-hydroxylase/17,20 lyase (CYP17A1) and aromatase (CYP19A1). The biological processes linked to these targets were concentrated on several pathways, including enzymes and hormones. Further experiments have revealed that minoxidil suppresses the expression of AR and CYP17A1, boosts the activity of CYP19A1, decreases the formation and binding of dihydrotestosterone, and enhances the production of estradiol. Through these changes, minoxidil acts as a treatment for AGA.Conclusion: Minoxidil may act by altering hormonal and enzymatic pathways. Our study finds two new targets (CYP17A1, CYP19A1) of minoxidil and demonstrates that minoxidil inhibits AR. These targets may provide new ideas for drug research.Keywords: minoxidil, androgenetic alopecia, targets